(untitled) (Jurnal Intek Akuakultur, 2019)
The study was used repelleting artificial feed with different consentration Sargassum sp. flour. The purpose of this research were to known the effect of Sargassum sp. On different consentration to the Survival rate of silver pompano. This research were held on June-July 2018 for 30 days at the Batam Marine Aquaculture Center, Setokok Island , Batam City, Riau Islands. The method was used experimental with a manual analysis were showed that Sargassum sp. Not given effect to the Survival rate of silver pompano. The result were showed that C treatment (40 g/kg) have the best on research parameters like absolute weight, and survival rate. They were 8,75Â±2,61 g, 93,33Â±0,00 % respectively.